Tirana Biennale 1. - Tirana Biennale 1, 2001; Antmen, Ahu; Arias, Fernando; Backstrom, Fia; Baldon, Diana; Balice, Daniele; Basta, Sarina; Basualdo, Carlos; Beatrice, Luca; Beecroft, Vanessa; Bernstrup, Tobias; Bertoli, Giasco; et al. (Milano : Giancarlo Politi Editore Milano, 2001)
A 12 ; Abdessemed, Adel ; Achour, Boris ; Agency ; Althamer, Pawel ; Amorales, Carlos ; Angellidakis, Andreas ; Arias, Fernando ; Arke, Pia ; Backstrom, Fia ; Bangboyé, Oladélé ; Basu, Sam ; Beecroft, Vanessa ; Beqiri, Sokol ; Bernstrup, Tobias ; Bertoli, Giasco ; Bertucci, Lina ; Beykal, Canan ; Bioy, Dimitry ; Björnsdottir, Olof ; Bodzianowski, Cezary ; Bonillas, Iñaki ; Boyadjiev, Luchezar ; Braun, Matti ; Breitz, Candice ; Breuning, Olaf ; Bruguera, Tania ; Büchel, Christoph ; Bulnygin, Dmitry ; Burrows, David ; Butzer, André ; Calvert, Mike ; Capelán, Carlos ; Carrier, Jacques ; Cattelan, Maurizio ; Cecchetti, Alex ; Charalambidis, Nikos ; Collins, Phil ; Crtalic, Marijan ; Cuoghi, Roberto ; Danwen Xing ; Décosterd & Rahm ; Decroux, Gérald ; Dejanov, Plamen ; Djurdjevic, Bilijana ; Djuric, Uros ; Dubossarsky & Vinogradov ; Ecua, Bola ; Escobar, Dario ; FA+ ; Feng Mengbo ; Fernández, Nicolas ; Fiuza Faustino, Didier ; Fonchain, Jérôme ; Francesconi, Luca ; Freeman, Jonah ; Gao Brothers ; Gavotta, Carlo ; Gjergji, Helidon ; Golia, Piero ; Görgün, Melih ; Gorlova, Ludmila ; Gorter, Bart ; Gramsma, Bob ; Graziani, Cristina ; Green, Jeff ; Griffiths, Brian ; Grüninger, Daniela ; Guzman, Daniel ; Hajdinaj, Alban ; Hakansson, Henrik ; Ham, Kyungah ; Harms, Bendix ; Harpaz, Alona ; Hassan, Jamelie ; Haxhillari, Besnik & Flutura ; Heger, Swetlana ; Hegue Yang ; Helfman, Michal ; Helmstetter, Kai ; Henry, Julie ; Hila, Edi ; Holmqvist, Karl ; Hornsleth, Kristian ; Hsia-Fei Chang ; Hvostov, Oleg ; Ivanov, Pravdoliub ; Jeane, Norma ; Judd, Ben ; Kadlec, Jan ; Kahlhamer, Brad ; Kerr, Andrew ; Klein, Micha ; Knall, Ulli ; Könitz, Alice ; Kostova, Daniela ; Krijnen, Cees ; Kumjim, Prapon Joe ; Kuri, Gabriel ; Kustov, Vladimir ; Kwaaitaal, Daniëlle ; etc.
biog. curatoren p. 487-490
Engels
Tirana Biennale 1 : Escape, National Gallery & Chinese Pavilion, Tirana, September 15 - October 15, 2001
kunstcatalogus